(untitled) (Research, Society and Development, 2022)
Cardiovascular changes related to COVID-19 are being increasingly reported, revealing the need for further investigations. In this context, the autopsy is capable of providing illuminating evidence. Therefore, the objective of this research was to synthesize the main cardiovascular findings of patients affected by COVID-19, based on autopsies. Methodology: A search was carried out in the CINAHAL, Embase, Google Scholar, IBECS, LILACS, MEDLINE, Science Direct, SciELO, Scopus, and Web of Science databases. Results: 29 studies were included, totaling 496 autopsies of men and women (27-94 years), mainly with a history of hypertension, obesity and diabetes. Autopsies revealed thrombi in multiple regions (lung, heart, kidneys, testicles); right ventricular dilation; abundance of megakaryocytes; viral presence in the heart; and myocarditis. Final considerations: COVID-19 has a complex interaction with the cardiovascular system, proving capable of interfering with its homeostasis, with thrombosis being the main pathophysiological event of this disease.